DAMPAK ENTERPRISE RISK MANAGEMENT PADA FUNGSI AUDIT INTERNAL - SHELVIA, LISA (: 2303-1719)
Society's growing demands for transparency, encourage each company to always be alert to risks in the activities that run the company. In the face of risk faced by the firm or the company's risk management need Enterprise Risk Management. Enterprise Risk Management is a common management application that specifically addresses strategies to address activities that pose a risk. Example of fraud committed employees. To minimize risks, it is necessary to Enterprise Risk Management is more effective so that it can increase its profit. Enterprise Risk Management is not done well will have an impact on the weakness of the internal audit function. That is, top management must play an active role in identifying, assessing, and managing enterprise risk, so that internal audit can provide assurance to the Board of Directors, Risk Management Committee, and related units in the company. With effective Enterprise Risk Management in the company can show that the main business risks have been managed well and the internal audit system has been running effectively.